PENGARUH SOCIAL MEDIA MARKETING DAN BRAND IMAGE TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI TOKO X.A.H.A.R.A KABUPATEN TASIKMALAYA - Neng Hasna Nabilah; Rina Madyasari; Alfin Nur Arifah; Yudi Setia Rachmanda (Journal Economics Technology And Entrepreneur, 2026)
This research is based on the phenomenon of declining sales experienced by the X.A.H.A.R.A store in Tasikmalaya Regency. The purpose of this study is to analyze the influence of Social Media Marketing and Brand Image, both individually and in combination, on consumer purchasing decisions at the X.A.H.A.R.A store in Tasikmalaya Regency. The method used is a quantitative approach, with descriptive and verification approaches. This study also involved respondents aged at least 17 years who had gone through the product purchasing process at the store. Primary data collection was conducted through the distribution of online questionnaires to 100 respondents selected using purposive sampling techniques, using the Cochran formula. The data analysis stage was completed with the assistance of SPSS statistical software. The results of the testing in this research confirm that strengthening Social Media Marketing strategies and building a solid Brand Image are crucial aspects for companies in stimulating consumer purchasing decisions.